Condition monitoring of a surface mounted permanent magnet‐type brushless direct current motor using remodelling of rotor magnetic field and stator winding inductance - Adil Usman; Bharat Singh Rajpurohit (IET Electrical Systems in Transportation)
Abstract The high‐performance characteristics of brushless direct current (BLDC) motor has made them indispensable for electric vehicle (EV) applications. The physical replacement of rotor windings with the permanent magnets on the rotor, makes the BLDC motor more compact, generating high torque‐power density. However, the continuous operation of BLDC motors in EVs make them vulnerable to faults. Develops the surface mounted permanent magnet‐type BLDC motor under healthy and fault conditions using remodelling of stator winding inductances and rotor magnetic fields of a machine. The stator winding inductance (LS) is modelled using winding function theory depending on the physical distribution of a winding, while the rotor magnetic field (Bg) is modelled through magnetic equivalent circuit based approach, respectively. Both the machine quantities under healthy operating conditions are estimated based on the motor geometry and validated numerically using finite element based methods. The experimental investigation validates the results obtained through given modelling techniques. The experimental and numerically obtained data of LS and Bg are then remodelled in a BLDC motor, to investigate the hybrid performance of a machine, useful in diagnosis of faults. The results obtained are further used to classify the faults and estimate its severity.